2010
DOI: 10.1016/j.disc.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Average distance and generalised packing in graphs

Abstract: a b s t r a c tLet G be a connected finite graph. The average distance µ(G) of G is the average of the distances between all pairs of vertices of G. For a positive integer k, a k-packing of G is a subset S of the vertex set of G such that the distance between any two vertices in S is greater than k. The k-packing number β k (G) of G is the maximum cardinality of a k-packing of G. We prove upper bounds on the average distance in terms of β k (G) and show that for fixed k the bounds are, up to an additive consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The k-packing number α k (G) of G is the cardinality of a maximum k-packing set [11]. For additional results on k-packing, see [4,10]. Moreover, k-packings are the key ingredients for the concept of the S -packing chromatic number (see [1,3,9] and references therein).…”
Section: Lower Bounds On Gp(g)mentioning
confidence: 99%
“…The k-packing number α k (G) of G is the cardinality of a maximum k-packing set [11]. For additional results on k-packing, see [4,10]. Moreover, k-packings are the key ingredients for the concept of the S -packing chromatic number (see [1,3,9] and references therein).…”
Section: Lower Bounds On Gp(g)mentioning
confidence: 99%
“…See [4], [26] for some references. The domination number and the k-distance domination number have moreover been related to the average distance of graphs in the recent papers [7], [8] and [9].…”
Section: Theorem 2 ([5]mentioning
confidence: 99%
“…Extremal problems for the mean distance were also examined in certain other classes of graphs [18], [13]. Chung [7] showed that the independence number is an upper bound the mean distance and Dankelmann [9] proved upper bounds for it in terms of the so called k-packing number. Average eccentricty (a distance related notion), was recently studied in [9].…”
Section: Introductionmentioning
confidence: 99%